Wittgenstein's Novels - Klebes, Martin (Studies in Philosophy, 2007)
Analyzing features of Wittgenstein's philosophical work and including in-depth textual analyses, this study investigates the impact of Ludwig Wittgenstein's work on contemporary German and French novelists. Drawing upon aesthetics, architectural history, philosophy of science, and photography, the book seeks to explain why references both to Wittgenstein as a person, as well as to his work are more pervasive than other equally renowned twentieth century philosophers and asks why some authors such as Händler and Roubaud, are less well-known and only partially translated into Eng.